Interest groups in Lithuania: dynamics of development and characteristics of institutionalization - Lukošaitis, Alvidas (Politologija, 2000)
The problems that are pertinent to the activities of the interest groups, their relationship with the State, etc., are obviously understudied in Lithuania. Therefore, in this article, the author embarks to ground the analysis by generalizing the empirical data. The focus of the study is to identify and analyze tendencies manifested during the initial institutionalization period of the interest group system. In this article, attempts are made to review and evaluate the specifics of the interest group development and to link these evaluations with the transformation of the political system. Owing to the lack of the interest groups’ studies in Lithuania, the author deprives his work of ambitious goals. At the same time, he tries to discover what direction the relationships between the State and the interest groups are moving towards – Pluralism, Corporatism, or "somewhere else." The article consists of the following parts: I. Theoretical Models for Analyzing Interest Groups; II. Institutionalization of Interest Groups in Lithuania; This part is divided into: 1. Transformation of the Soviet political system and the interest groups; 2. Founding of the legal environment for interest groups and stages of their development in Lithuania; III. Organized Interests: Representation of Capital and Labor Interests in Lithuania; This part is further divided into: 1. Organized Labor interests – Labor Unions; 2. Organized Labor and Employers’ interests; 3. Labor, Business, and State interests: trilateral cooperation, cooperation, and coordination of interests. Seeking to present historical insight into the literature related to the issue of the interest groups, the way they were defined and the problems that were once attached to them and their activities, their place within society, the author refers to J. Madison, A. de Tocqueville, A.F. Bentley, D. Truman, M. Olson, K. Middlemas, G. Wilson, and other scholars. In the first part of the article, the author presents and studies the theoretical models for analyzing interest groups. He states that in liberal democracies, two methodological models are used to ground the research of interest groups, namely, Pluralism and Corporatism. Characteristics, which describe the pattern of interrelationship between the interest groups and the Government, first in Pluralist, later in Corporatist States, are presented. The former is based on references to such scholars like Day and Zeigler, Žeruolis, etc., the latter – on Schmitter. By introducing and elaborating on the third pattern of interrelationship between the State and the interest groups – Clientelism – the author moves over to a comparative analysis of the three. For that sake, Zink is referred to. In the second part of the article, the author first discusses the theoretical premises of interest group functioning and activities in the Soviet systems, based on Skilling’s classical 1966 work and 1993 Cox’s piece, later adopts basic comparative differences between the western and the Soviet patterns of the relationship between the State and the interest groups. The author presents three stages of evolution of this pattern in the Soviet political system: 1) before 1985; 2) the period between 1985–1990; and 3) the period starting from 1990. Specifics and consequences of each of these periods are depicted. With that token, the author takes upon the load to elaborate on the process of founding the legal environment for interest groups and stages of their development in Lithuania. Scholars from Lithuania and foreign countries are oftentimes cited. The mentioned three stages are embarked as a framework. Within them, the author elucidates several phases. In the third part, the author presents the empirical data, generalizes, and classifies it in order to meet the core objective of the study – to ground the analysis of the pattern of interrelationship between the State and interest groups in Lithuania. The part is divided into three subparts, namely, Organized Labor interests – Labor Unions; Organized Labor and Employers’ interests; Labor, Business, and State interests: trilateral cooperation, cooperation, and coordination of interests. The interest groups topic is wide: analysis of the methods concerning the reasons for birth, organizational structure, and methods of activity can be treated as a starting point for scientific research, whereas the ending point of the research could be reserved for studying the patterns of interest groups – state relationships. In this article, the scope of research is limited to three problems. First, the author tried to grasp the connection (and causes) between the changing communist society and the evolution of new interest groups. Second, the author tried to identify the limits of action as delineated by the State with regard to the interest groups. The third problem might be that by using the first two parameters, the author tried to evaluate the initial institutionalization specifics of the interest groups and, by that token, identify the pattern of interaction between the State and the interest groups. Author concludes that the rate of transformation and democratization of the political system in Lithuania determined that the dispersion of the interests in society has been carried very dynamically. He regrets that the volume of the work stood as an obstacle for attempts to analyze the extent the outburst and proliferation of the interest groups surpassed the differentiation of the society itself, and, besides, understand whether this process concurred the new needs of the free market economy. It is said that within the context of the mature political system the pace and dynamics of interest groups evolution were not something outstanding: some years were required to legitimize their activities, as it often happens, the interest groups have to search for the support base in the society, their material basis, human and other resources - scarce. Interestingly, abundance of the interest groups from different sectors stimulates competition, which, oftently urges them to revise the aims and methods of their activity. Gradually the interest groups free themselves from ideologized understanding of their activities, differences concerning the status of their political organizations and themselves come to the fore as well. Author concludes that the most complicated affairs is to describe the relationships between the State and the interest groups. The reason for that, the author says, is simple - still too little time has passed before the activities of the interest groups could be treated as an institutionalized phenomenon. Author expresses doubts whether the pattern of interaction of the State and the interest groups in Lithuania could be described as pluralistic. He gives following reasons for that: first, it is obvious that the political process in Lithuania is neither fragmented, nor dispersed. Besides, State institutions and interest groups are far from being equal partners. On the contrary, the Government oftentimes comes to openly ignore the interest groups. Second, there are no terms of equality and uniform competition among the interest groups themselves - decisions in public politics remind from time to time that some of the groups, due to some reasons, are more equal than others. According to the author, it is even more difficult to test whether this pattern of interrelationship corresponds to the criteria of Corporatism. On the one hand, Corporatism implies coordination of links between the State and the interest groups. On the other - it implies functional inclusion of the interest groups into the decision-making process. Besides, it is characterized by that the State treats interest groups selectively when the pragmatic outlook and specialization of the interest groups in some spheres allows them to depoliticize a number of policy sectors. Efforts of the State to coordinate (sometimes, even aggressively "interfere" in places it should not) the activities of the interest groups in Lithuania are obvious. This proposition is supported by, for example, the activities of the Trilateral Council, which gains effectiveness, influence of the State upon the Trade, Industry and Handicraft House. However, such efforts not always imply effect satisfying every side. Oftentimes, the interest groups express their dissatisfaction with the State, which, according to them, ignores their opinion and passes the decisions that are not political in sense that they ruin business, agriculture and so on. Such situation could infer that the organized interests still come to confront the syndrome of "deafness" and "blindness" on the governmental level. Number of features characteristic to patronage and Clientelism are also observed in contemporary relationships between the State and interest groups. Interest groups are not so strong or influential as to compete with the power and influence of political elite in the decision-making process. Therefore, much, will the interests groups be taken into account or not, depends on the mercy of the latter. Corruption, bribes, lack of transparency in questions like financing of the political campaigns and parties, - all these are the facts proving that the interest groups, which are not allowed to act in ways pertinent to civilized and democratic societies, are forced to act by employing totally different methods.